Use of prescription and nonprescription medications and supplements by cancer patients during chemotherapy: questionnaire validation - Hanigan, Marie H; dela Cruz, Brian L; Thompson, David M; Farmer, Kevin C; Medina, Patrick J (Journal of oncology pharmacy practice, 2008)
Background. Cancer patients take medications for coexisting disease and self-medicate with over-the-counter drugs (OTCs). A complete analysis of the use of prescription drugs, OTCs, and supplements during cancer treatment has never been done. Methods. The study developed and validated a self-administered questionnaire on the use of concomitant medications by patients undergoing treatment with chemotherapy. The questionnaire listed 510 prescription medications, OTCs, and supplements (including vitamins, minerals, and herbs). Fifty-two subjects completed the questionnaire while visiting the infusion clinic to receive chemotherapy. On a subsequent visit the subjects brought their medications to the clinic and a pharmacist reviewed their completed questionnaire. Results. Ninety-six percent of the subjects reported taking prescription medications within 3 days prior to chemotherapy, 71% reported taking OTCs and 69% reported use of supplements. The subjects took an average of 5.5 (range 0—13) prescription drugs, 2.2 (0—20) OTCs, and 1.9 (0—11) supplements. Twenty-one drugs were each taken by at least 10% of the subjects. Acetaminophen was taken by 59.6% of the subjects. One subject reported taking five acetaminophen-containing drugs. The questionnaire's sensitivity was 92.0%, specificity 99.9%. Conclusion. Within 3 days prior to chemotherapy, subjects took an average of 9.6 concomitant medications, many of which alter drug metabolism and or disposition. In clinical trials, multivariate analysis of all concomitant medications could add to clinically relevant data to identify drug interactions that negate or potentiate the efficacy of cancer treatment regimens. In some instances, apparent resistance of tumors to chemotherapy may be the result of drug interactions. J Oncol Pharm Practice (2008) 14: 123—130.